Emerging Information Technologies in Accounting and Related Security Risks – What Is the Impact on the Romanian Accounting Profession - Sînziana-Maria Rîndașu (Journal of Accounting and Management Information Systems (JAMIS), 2017)
This study investigates whether aspiring and professional accountants understand the benefits and security challenges brought by emerging technologies such as: Big Data, data analytics, cloud computing and mobile technologies. 115 participants took part in a survey during January and February 2017, all having at least one year of practical experience in accounting or audit and 80% of them being affiliated with national or international accounting professional bodies. The research has three key findings: (1) Professional accountants and auditors are having in average a theoretical knowledge of the emerging technologies in the accounting field, but they still need to enhance their skills to exploit them efficiently, (2) Mobile technologies started to be adopted by the Romanian practitioners and (3) The profession has become aware of the security risks brought by emerging technologies in the digital accounting. The accounting profession is on the verge of change and the practitioners do not yet possess sufficient skills regarding the analyzed emerging technologies. As per this, the professional bodies and academic environment should reassess their curricula to enforce the necessary changes for preparing practitioners to successfully face the future challenges and avoid their replacement by other professions more qualified.
Keywords: L86; M41; O33; 650; cloud computing; mobile technologies; Big Data; data analytics; security threats